University of the Future - Ahmad Dahlan, Abdul Rahman; Shihab Ahmed, Ahmed; Yao, Li Yao (Eclat Research Publication, 2014)
Future is a beautiful word with unlimited imaginations. We need to be reality regardless how many fancy ideas we have about future. At the contemporary age, we experience changes every single day, so as our universities. By deploying the relationship among academic, industry, and government, it formed an emergent entrepreneurial paradigm in which the university plays an important role in technological innovation. In this paper, we are going to apply our fruitful ideas and concepts about the University of Future based on survey, interviews and two types of analytical tools which are Business Model Canvas and Value Proposition Design to conduct an ideal business model for our university of future. Base on the application of different tools and methodology, we found out that the University of Future Needs to be innovative, flexible, and value-added as well as advanced technology utilities. As the data and information are collected in limited basis, the finding might not be comprehensive in certain extent.